Oncogenomics and Cancer Proteomics Novel Approaches in Biomarkers Discovery and Therapeutic Targets in Cancer - López-Camarillo, César; Aréchaga-Ocampo, Elena (IntechOpen, 2013)
Oncogenomics and Cancer Proteomics - Novel Approaches in Biomarkers Discovery and Therapeutic Targets in Cancer presents comprehensive reviews of the most common cancers from bench to bedside applications by an international team of experts. This book will contribute to the scientific and medical community by providing up-to-date discoveries of oncogenomics and their potential applications in cancer translational research. It is intended for students, scientists, clinicians, oncologists and health professionals working in cancer research.